Antioxidant and antibacterial activities of the rhizome extract of Curcuma zedoaria extracted using some organic solvents - Budiansyah, Agus; Haroen, Ucop; Syafwan, Syafwan; Kurniawan, Kiki (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This research aims to identify the effect of various organic solvents such as n-hexane, ethyl acetate (EtOAc), and methanol (MeOH) on the antioxidant and antibacterial activities of Curcuma zedoaria extract, against three Gram-positive bacteria, namely Staphylococcus aureus, Bacillus subtilis, and Streptococcus pneumoniae, and three Gram-negative bacteria, namely Escherichia coli, Salmonella typhi, and Pseudomonas aeruginosa. Materials and Methods: As much as 1 kg of white turmeric rhizome (C. zedoaria) was extracted two times for 24 h using 3 l of MeOH before evaporating. The extract was then fractionated using n-hexane six times per 2 h, with each volume of 500 ml, and continued with the EtOAc fractionation. The MeOH fraction was added to 300 ml of water before adding 400 ml of EtOAc. Once the fractionation process was complete, all fractions were concentrated using a rotary evaporator. Results: The C. zedoria extract fractioned using MeOH produces alkaloids, phenolics, flavonoids, saponins, and coumarin compounds. The fractionation with EtOAc also produces alkaloids, phenolics, flavonoids, saponins, coumarin compounds, and triterpenoids. Meanwhile, fractionation with n-hexane only produces alkaloids and triterpenoid compounds. EtOAc and MeOH fractions had good activity in reducing free radicals produced by 2,2-diphenyl-1-picrylhydrazyl (DPPH), with an average IC50 value of 153.49 ± 2.66 and 185.77 ± 3.91 ppm, respectively. In contrast, the n-hexane fraction has weak antioxidant activity with an IC50 value of 837.92 ± 5.32 ppm. The n-hexane fraction has better activity compared to MeOH and EtOAc. The lowest concentration required was 2,500 ppm for all types of bacteria. Conclusion: Curcuma zedoaria extract produces alkaloids, phenolics, flavonoids, saponins, coumarins, and triterpenoids when fractionated with MeOH or EtOAc. Only alkaloids and triterpenoids are produced using n-hexane. EtOAc and MeOH fractions have good activity in reducing free radicals generated by DPPH, with an average IC50 value of 153.49 ± 2.66 and 185.77 ± 3.91 ppm, respectively. However, n-hexane has weak antioxidant activity, with an average IC50 value of 837.92 ± 5.32 ppm. All fractions have moderate antibacterial activity, but the extract of n-hexane from C. zedoary has better antibacterial activity compared to MeOH and EtOAc. The lowest concentration required is 2,500 ppm for all types of bacteria. J. Adv. Vet. Anim. Res., 10(3): 347–360, September 2023 http://doi.org/10.5455/javar.2023.j687